The Effectiveness of Alkaline Water Consumption and Walking Exercise on the Quality of Life of Diabetes Mellitus Patients at the Pratama Yakri Clinic - Malik Ibrahim; Tri Mochartini (Universitas Malahayati Lampung, 2024)
ABSTRACT In 2022, the International Diabetes Federation (IDF) recorded that 537 million adults (aged 20-79 years) or 1 in 10 people live with diabetes worldwide. Diabetes also causes 6.7 million deaths or 1 every 5 seconds. China is the country with the largest number of diabetes sufferers in the world, 140.87 million people. Furthermore, India is recorded as having 74.19 million people with diabetes, Pakistan 32.96 million, and the United States 32.22 million. Indonesia is in fifth position with the number of diabetes sufferers of 19.47 million. A person suffering from Diabetes Mellitus will have a disrupted quality of life. Apart from walking, non-pharmacological treatment that can be done by type 2 diabetes mellitus sufferers is by consuming alkaline water with a PH 8. To determine the effectiveness of consuming alkaline water and walking exercise on the quality of life of diabetes mellitus patients. Quasi experiment with a posttest group design. The sample in this study was all 40 diabetes mellitus patients at the Pratama Yakri Clinic in Jakarta in December 2023. The sampling technique uses total sampling. The majority of respondents in the intervention group had good quality of life (70.0%), in the majority group their quality of life was very poor (75.0%). Alkaline water consumption and walking exercise are effective in improving the quality of life of diabetes mellitus patients (p value 0.000). Consuming alkaline water and walking exercise are effective in improving the quality of life of diabetes mellitus patients. It is hoped that diabetes mellitus sufferers will carry out activities such as walking and consuming alkaline water to improve their quality of life. Keywords: Walking Exercise, Alkaline Water, Diabetes Mellitus, Quality Life